Evaluation of Bone Marrow-derived Stem Cells and Adipose-derived Stem Cells Co-cultured on Human Nucleus Pulposus Cells: A Pilot Study - Yoon, Sang Hoon; Kim, Dae Hee; Cho, Sam; Kim, Ki-Jeong (Korean journal of neurotrauma, 2020)
We aimed to determine whether bone marrow-derived mesenchymal stem cells (BDMSCs) effectively attenuate the degeneration of human nucleus pulposus cells (NPCs). Four NPC lines were obtained from 3 subjects who underwent spinal surgery for cervical disc herniation (n=1) or lumbar disc herniation (n=2). For co-culture wells without contact, BDMSCs and adipose-derived mesenchymal stem cells (ADMSCs) were seeded on tissue culture plates and maintained for 3 days. Senescence-associated β-gal (SA-β-gal) staining was represented as a percentage of the total number of stained cells (%). The cells with intracellular lipid droplets (LDs) were represented as the percentage of the number of cells with LDs. Glycosaminoglycan (GAG) secretion was measured at 450 nm, using a commercial kit, to analyze optical density. The ratio of cells stained with SA-β-gal to the total number of cells reduced significantly when co-cultured with BDMSCs and ADMSCs ( <0.001 vs. <0.001). The proportion of NPCs containing LDs was lower when co-cultured with BDMSCs than with ADMSCs ( <0.001). The optical density related to GAG secretion was lower in BDMSCs and ADMSCs co-cultured with NPCs than in the controls ( <0.001 vs. <0.001). SA-β-gal staining showed significant attenuation of degenerative changes in NPCs co-cultured with BDMSCs. Moreover, the unexpected increase in LDs was significantly higher in NPCs co-cultured with ADMSCs than in those co-cultured with BDMSCs. However, GAG secretion was significantly decreased in NPCs co-cultured with MSCs.